Remediation of wastewater by biosynthesized manganese oxide nanoparticles and its effects on development of wheat seedlings - Ishfaq, Aneeza; Shahid, Muhammad; Nawaz, Muhammad; Ibrar, Danish; Hussain, Sabir; Shahzad, Tanvir; Mahmood, Faisal; Rais, Afroz; Gul, Safia; Gaafar, Abdel-Rhman Z.; Hodhod, Mohamed S.; Khan, Shahbaz (Frontiers in Plant Science, 2023)
Nanoparticles play a vital role in environmental remediation on a global scale. In recent years, there has been an increasing demand to utilize nanoparticles in wastewater treatment due to their remarkable physiochemical properties. In the current study, manganese oxide nanoparticles (MnO-NPs) were synthesized from the Bacillus flexus strain and characterized by UV/Vis spectroscopy, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. The objective of this study was to evaluate the potential of biosynthesized MnO-NPs to treat wastewater. Results showed the photocatalytic degradation and adsorption potential of MnO-NPs for chemical oxygen demand, sulfate, and phosphate were 79%, 64%, and 64.5%, respectively, depicting the potential of MnO-NPs to effectively reduce pollutants in wastewater. The treated wastewater was further utilized for the cultivation of wheat seedlings through a pot experiment. It was observed that the application of treated wastewater showed a significant increase in growth, physiological, and antioxidant attributes. However, the application of treated wastewater led to a significant decrease in oxidative stress by 40%. It can be concluded that the application of MnO-NPs is a promising choice to treat wastewater as it has the potential to enhance the growth, physiological, and antioxidant activities of wheat seedlings.